The role of access convenience of common service centres (CSCs) in the continued use of e-government. Issue 5 (7th December 2020) - Gupta, Kriti Priya; Maurya, Harshit
Abstract : Purpose: This study aims to understand the role of access convenience of common service centres (CSCs) in determining the e-government continuance intention from the perspective of citizens who are dependent on these centres for using e-government services, in developing countries such as India. The study uses the DeLone and McLean's information systems (IS) success model as a theoretical basis and analyses the effect of access convenience of CSCs (AC), on the three quality dimensions (namely, information quality [IQ], system quality [SyQ] and service quality [SQ]), and the e-government continuance intention. The effects of the three quality dimensions on continuance intention are also analysed. Design/methodology/approach: The primary data were collected from the field surveys conducted at various CSCs in Uttar Pradesh state of India using convenience sampling technique. The study sample included 358 respondents who use e-government services through CSCs. Structural equation modelling was used to test the hypothesized relationships in the proposed model. Findings: The findings of the study suggest that CSCs' access convenience has a significant positive impact on the e-government continuance intention. The findings also confirm the significant positive impact on all the three quality dimensions of e-government i.e. IQ, SyQ and SQ. Though the findings do not provide support for the impact of IQ and SyQ on the e-government continuance intention but the impact of SQ on the e-government continuance intention is found to be significantly positive. Research limitations/implications: The explanatory power of the model indicates the scope of including more variables in determining the continued usage of e-government. Future studies may extend the present study by including concepts such as trust, satisfaction and security/privacy concerns of citizens. The present study has failed to support the impact of IQ and SyQ on the intention to continue using e-government services. Future studies may test the model in different contexts with different respondents to further examine these relationships. Future studies may also see the association between the continuance intention and actual use of e-government services. Practical implications: The government should provide accessible CSCs to the citizens which are conveniently available to them. To diffuse the e-government services successfully among all citizens, the government needs to see that sufficient numbers of CSCs are available in the areas where people lack the required infrastructure for using the e-government services. The government also needs to ensure that the CSCs are fully functional and equipped with facilities for providing the best quality services. Originality/value: The study combines the quality constructs from the IS success model with AC, for predicting the e-government continuance intention. The joint use of these constructs has provided a model with high explanatory power, which is able to explain 76.6% variation in the continued usage of e-government services. The study also contributes to the existing literature by presenting AC as a strong determinant of the e-government quality dimensions.